Prebiotics Activity of Laminaran Derived From Sargassum crassifolium - Anies Chamidah; Hardoko Hardoko; Asep Awaludin Prihanto (Research Journal of Life Science, 2016)
The objectives of this study were to evaluate the prebiotic activity based on the change in cell biomass of the probiotic strain after 24-h growth in the presence of Laminaran from Sargassum crassifolium with the methods of laminaran acid extract (LAE) and laminaran modified extract (LME), inulin, or glucose-relative against the change in cell biomass of Escherichia coli FNCC 0091 grown under the same condition. Prebiotic activity was calculated for L. plantarum FNCC 0051 and Bifidobacterium longum FNCC 1081. The results showed that the increasing cell number of L. plantarum was higher in both substrates LAE and LME (0,58 and 2,03log cycle), whereas that of B. longum was lower. The higher prebiotic activity score obtained for L. plantarum and B. longum grown on LME were positive (0,26 and 0,96 log cycle), whereas the lowest score was for L. plantarum and B. longum grown on LAE, which were negative (-0,35 and -0,31 log cycle), but the higher prebiotic activity score was obtained for inulin (4,08 and 4,78 log cycle). It could be concluded that Laminaran Modified Extract (LME) has potential as prebiotic source, but its potential was lower than inulin.